PENERAPAN METODE REMINDER DENGAN APLIKASI SHORT MESSAGE SERVICE DAN WHATSAPP UNTUK MENINGKATKAN KEPATUHAN KUNJUNGAN ANTENATAL DI PUSKESMAS LAPE - Nur Ike Putri; Has’ad Rahman Attamimi; Luh Putu Sri Yuliastuti (LPPM STIKES Griya Husada Sumbawa, 2021)
The most common causes of maternal death in NTB province in 2017 occurred when pregnant women were 17.65%, during childbirth 42.35%, and during childbirth by 40% (NTB Provincial Health Office, 2017). The purpose of this study was to determine the application of the reminder method using short message service (SMS) and the whatsapp application to improve antenatal visit compliance. This study uses observational data collection methods with research design is action or action research with the number of respondents 35 pregnant women. Data analysis uses interactive analysis, namely data collection, data reduction, data presentation, and drawing conclusions according to Miles and Huberman (2015). The results of this study indicate that the adherence of pregnant women to antenatal visits in the first cycle there are 27 people (77.14%) obedient and 8 people (22.85%) not compliant by using the SMS application, while using the Whatsapp application there are 24 people (68 ,57%) complied and 11 people (31.42%) did not comply. In cycle II there were 35 people (100%) obedient by using the SMS application, while using the Whatsapp application there were 33 people (94.28%) obedient and 2 people (5.71%) not. This proves that the action research method is effective in using the reminder method with SMS and WhatsApp applications in improving antenatal visit compliance in the working area of the Lape Health Center, Lape sub-district.